Knowledge mapping of immunotherapy in cervical carcinoma: a bibliometric analysis (2000-2023) - Song, Ling; Liang, Xinmei; Zhu, Min; Su, Qiang; Li, Fengzhou (Frontiers in Immunology, 2024)
Background Cervical carcinoma is a type of malignant tumor that primarily develops in the cervix, the lower part of the uterus. In recent years, Despite the considerable progress made in immunotherapy research for cervical carcinoma, an important aspect has been largely overlooked - the absence of a comprehensive bibliometric analysis in this field. By employing bibliometric techniques, this study aims to fill this gap and provide a comprehensive overview of the knowledge structure and research hotspots within the realm of immunotherapy in cervical carcinoma. Method A comprehensive search was conducted on the web of science core collection(WoSCC) database to identify publications related to immunotherapy specifically for the treatment of cervical carcinoma. The search spanned the period from the year 2000 to 2023. Several analytical tools were employed. These included VOSviewers, CiteSpace, and the R package “bibliometrix”. Results A total of 654 research articles from 66 different countries have been included in the analysis. The United States and China have emerged as the leading countries in publishing research on immunotherapy in cervical carcinoma. Leiden University and Memorial Sloan-Kettering Cancer Center from the Netherlands and the United States respectively have a close cooperation. Fudan University from China and the German Cancer Research Center are also among the key institutions leading research in this area. Frontiers in Oncology has emerged as the most popular and widely recognized publication in the field of immunotherapy in cervical carcinoma. Journal of Clinical Oncology is frequently cited by researchers in this area. Van Der Burg, Sjoerd H has published the highest number of papers. Tewari, Krishnansu S has been the most co-cited author. Keywords such as PD-L1, chemotherapy, and immune checkpoint inhibitors have gained significant attention in recent years. Conclusion This is the first bibliometric study that comprehensively summarizes the research trends and developments of immunotherapy in cervical carcinoma. This groundbreaking study not only summarizes the current research trends and developments in immunotherapy for cervical carcinoma but also provides a reference for scholars studying the treatment of cervical cancer.